Book clubs : women and the uses of reading in everyday life - Long, Elizabeth (University of Chicago Press, 2003)
Book clubs are everywhere these days. And women talk about the clubs they belong to with surprising emotion. But why are the clubs so important to them? And what do the women discuss when they meet? To answer questions like these, Elizabeth Long spent years observing and participating in women's book clubs and interviewing members from different discussion groups. Far from being an isolated activity, she finds reading for club members to be an active and social pursuit, a crucial way for women to reflect creatively on the meaning of their lives and their place in the social order.